INTERRALATIONS OF REOCARDIOGRAPHIC PARAMETRES OF CENTRAL HEMODINAMICS WITH CONSTITUTIONAL INDICATORS BY VOLLEYBALL PLAYERS OF DIFDERENT POSITIONS - Yakusheva, Yu.I.; Sarafynyuk, L.A.; Kyrychenko, Y.V. (World of Medicine and Biology, 2015)
Correlations between indicators of central hemodynamics, which were obtained by tetra polar reocardiography and anthropometric dimensions, components of somatotype and body weight in youth volleyball high level of sportsmanship, were established in the article. It was found that by setters and hitters all 12 central hemodynamic parameters have a significant correlation with the constitutional characteristics, but libero have only 8. The power of ligament is the highest in the group of libero. In all groups of volleyball players the specific peripheral resistance and cardiac index have the largest and most strength of correlation with somatic parameters.
Keywords: correlation; central hemodynamics; anthropometry; somatotype; components of body weight; volleyball players; position